OPTIMALISASI KINERJA PAURTAP BERBASIS APLIKASI DATATABLE DALAM PENGELOLAAN DATA PNS DI AJEN AKMIL - Sri Mustika Wardani; Asep Hanry Putrantono (PPM Sdirjianbang Akademi Militer, 2023)
Along with the rapid development of information and communication technology, it requires the development of modern information and technology to be applied to the TNI AD environment, especially the Adjutant General Corps which deals with Moral Welfare, General Administration and Personnel Administration activities which require the movement of information and data via the internet effectively and efficiently so that research This aims to determine the quality of the performance of Officers of Affairs in optimizing the facilities and infrastructure of the Ajen Akmil unit in managing PNS TNI AD personnel data and to find out the driving forces and constraints of the Ajen Military Academy in realizing online PNS data information technology. This research is a qualitative research with data collection techniques using qualitative methods, namely describing existing phenomena, non-research observations, in-depth interviews, documentation, and detailed data collection using various data collection procedures and in continuous time. The results of the study explain that the Service Quality of the Ajen Akmil as a unit that manages and carries out the functions of duties and responsibilities in a fast, precise, correct, orderly and smooth manner by utilizing advances in Information Technology. So that the solution taken to answer the constraints and problems found in the Ajen Akmil unit is to improve the quality of human resources through education and training activities that are more frequent and focused on technological developments to support the effectiveness of digital data management. And not only that by using a data table application to accommodate local administrative activities within the Military Academy Institution.Therefore, in order to improve the quality of personnel administration activities, especially in the field of personnel data management, it is suggested to the Ajen Akmil unit to give positions to Ajen personnel according to their field of educational specialization, to be able to conduct outreach about personnel administration activities to all personnel in the Military Academy Institute and to require every Ajen Akmil personnel to carry out Dikbangspes according to their respective positions.